A K band self‐packaged SISL Rotman lens antenna array using low‐cost FR4. Issue 2 (16th November 2021) - Zhang, Guoshuai; Ma, Kaixue; Yan, Ningning; Luo, Yu; Fu, Haipeng
Abstract: A Rotman lens antenna array with advantages of self‐packaging, low cost, and broadband is proposed by using substrate integrated suspended line technology at K band. The proposed lens‐fed antenna is designed to be low cost by using only FR4 material on all substrates. Meanwhile, patterned substrate and double metal layers with metalized via hole connecting are utilized to reduce its loss. To evaluate the proposed method, two Rotman lenses with different port numbers are designed, fabricated, and measured. For verification of switch beam property, the quasi‐Yagi antenna array is designed for broadband operation and low profile to integrate with the Rotman lens. The experimental results show that the scanning range is ±24° and ±30° of the two lenses, respectively.